Systemic arterial hypertension and cognition in adults: effects on executive functioning - MORAES, Natália Cristina; MUELA, Henrique Cotchi Simbo; MEMÓRIA, Claudia Maia; COSTA-HONG, Valéria Aparecida da; MACHADO, Michel Ferreira; CECHINHI, Mario Amore; NITRINI, Ricardo; BORTOLOTTO, Luiz Aparecido; YASSUDA, Monica Sanches (Arquivos de Neuro-Psiquiatria, 2020)
Background: Central nervous system changes associated to systemic arterial hypertension (SAH) are progressive and may cause negative effects on cognitive performance. The objective of this study was to investigate the relation between SAH and the components of executive functions (EF), inhibitory control (IC), updating and shifting, comparing a control group (without SAH) to patients with SAH, in two levels of severity. Methods: The protocol included the following tests to evaluate EF components: T.O.V.A. Test (IC), Backward Digit Span from Wechsler Adults Intelligence Scale (WAIS-III), Phonemic and Semantic Verbal Fluency (updating), and Trail Making Test Part B (shifting). Results: A total of 204 participants was included: 56 from the Control Group (CG), 87 SAH stage 1, and 61 SAH stage 2. The groups were not different for age (52.37±12.29) and education (10.98±4.06). As to controlled blood pressure (BP), duration of hypertension treatment and number of drugs, the SAH 2 group had a worse BP control, longer duration of hypertension treatment and use of more drugs when compared to the SAH 1. The findings revealed that patients with more severe hypertension presented worse performance in updating (Backward Digit Span, phonemic and semantics VF) and shifting (Trail Making Test Part B). Conclusion: The results suggest that patients with SAH have a significant impairment in EF, more specifically in updating and shifting. Besides that, such damage may be directly proportional to the severity of SAH. It is suggested that future studies include neuroimaging exams to exclude possible cerebrovascular diseases.
Keywords: Hypertension; Cognition; Executive Function